Nothing ever just disappears : seven hidden queer histories - Hester, Diarmuid, 1982- (Pegasus Books, 2024)
Both thought-provoking and eye-opening, this radical new history of seven queer lives, including Josephine Baker in Paris and E.M. Forster in Cambridge, illuminates the connections to where they lived, who they loved and the art they created, and celebrates freedom, survival and the hidden places of the imagination.